The «Salvific Capacity Principle» in Adolphe Gesché’s Theology - García-Mourelo, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
Adolphe Gesché established the «salvific capacity principle» —salutarité— as the proper task of Theology. Theology had to be able to propose the intelligibility of the Christian faith concepts in order to rediscover God and the salvation that only he can give. This study presents this principle, its origin and meaning, as well as its development in Dieu pour penser. It shows its possibilities —against the existence limits—, its foundation —filiation—, its proposal —divinisation— and its actualisation —revelation—.